Health worker perspectives on the possible use of intramuscular artesunate for the treatment of severe malaria at lower-level health facilities in settings with poor access to referral facilities in Nigeria: a qualitative study. Issue 1 (December 2016) - Adesoro, Olatunde; Shumba, Constance; Kpamor, John; Achan, Jane; Kivumbi, Harriet; Dada, John; Maxwell, Kolawole; Tibenderana, James; Marasciulo, Madeline; Hamade, Prudence; Oresanya, Olusola; Nankabirwa, Joanita; et al.
Abstract Background Innovative strategies are needed to reduce malaria mortality in high burden countries like Nigeria. Given that one of the important reasons for this high malaria mortality is delay in receiving effective treatment, improved access to such treatment is critical. Intramuscular artesunate could be used at lower-level facilities given its proven efficacy, ease of use and excellent safety profile. The objective of this study was therefore to explore health workers' perspectives on the possible use of intramuscular artesunate as definitive treatment for severe malaria at lower-level facilities, especially when access to referral facilities is challenging. The study was to provide insight as a formative step into the conduct of future experimental studies to ascertain the feasibility of the use of intramuscular artesunate for definitive treatment of severe malaria in lower level facilities where access to referral care is limited. Methods This qualitative study was done across three southern States in Nigeria (Oyo, Cross River and Enugu). Key informant interviews were conducted over a period of three months between October and December 2014 among 90 purposively selected health workers with different roles in malaria case management from primary care to policy level. A thematic content analysis was used to analyse data. Results Overall, most of health workers and other key informant groups thought that the use of intramuscular artesunate for definitive treatment of severe malaria at lower-level facilities was possible. They however reported human resource and infrastructure constraints as factors affecting the feasibility of intramuscular artesunate use as definitive treatment for severe malaria in lower-level facilities.. Specifically identified barriers included limited numbers of skilled health workers available to manage potential complications of severe malaria and poorly equipped facilities for supportive treatment. Intramuscular artesunate was considered easy to administer and the proximity of lower-level facilities to communities was deemed important in considering the possibility of its use at lower-level facilities. Health workers also emphasised the important role of operational research to provide additional evidence to guide the implementation of existing policy recommendations and inform future policy revisions. Conclusions From the perspective of health workers, use of intramuscular artesunate for definitive treatment of severe malaria at lower-level health facilities in Nigeria is possible but dependent on availability of skilled workers, well-equipped lower-level facilities to provide supportive treatment There is need for further operational research to establish feasibility and guide the implementation of such an intervention.